„Kämpfe“ um die legal person: Wie Unternehmen von ihrem Personencharakter profitieren - Matys, Thomas (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
The article discusses how corporations in the U.S., mostly economic, have managed over the last 200 years to claim human rights elaborated in the U.S. Constitution for themselves (e. g. the right due process of law, or free political speech). A multitude of court rulings offer a wealth of empirical material. In the United States an evergrowing critical movement has attempted to criticize and scandalize such corporate rights. An analysis derived from sociology and Political Economy can show that gaining such corporate rights, can be referred to as an increasing privatization of political power and as a historical institutionalization of the - nowadays globally applicable - corporate form.